Tingkat Kebisingan pada Angkutan Umum Jalur Teling-Pusat Kota Manado - Liono, Marlisha C. B.; Pelealu, Olivia C. P.; Mengko, Steward K. (Universitas Sam Ratulangi, 2020)
Abstract: Noise is all unwanted sounds that can cause discomfort feeling or hearing disturb-ance if be exposed for long enough. Moreover, it can disturb the surrounding environment due to the generated noise. In Manado, many public transportation have audio system to play high volume music, therefore, causing noise. This study was aimed to determine the level of noise in public transportation of Teling to Manado downtown track. This was a descriptive and observational study with a cross sectional design. Samples were 100 vehicles of Teling to Manado downtown track. Noise measurement was performed by using a sound level meter. Data were analyzed by using Microsoft Office Excel. The results obtained 56 vehicles with audio systems and 44 vehicles without audio systems. Among 56 vehicles with audio systems, there were 47 vehicles that had noise levels above the noise threshold value which was 86.05-114.15 dB with exposure time about 8-16 hours. Meanwhile, among 44 vehicles without audio system, there were only 2 vehicles that had noise levels above threshold value which was 88.05-91.8 dB with exposure time about 10-12 hours. In conclusion, there were 49% of public vehicles had noise level above the threshold value.Keywords: noise; public transportationÂ Abstrak: Kebisingan adalah semua bunyi yang tidak dikehendaki yang dapat menimbulkan ketidaknyamanan atau gangguan pendengaran jika terpapar lama. Selain itu kebisingan dapat juga mengganggu lingkungan sekitar. Di Kota Manado, banyak angkutan umum yang menggunakan sistem audio untuk memutar musik dengan volume yang tinggi sehingga menimbulkan kebisingan. Penelitian ini bertujuan untuk mengetahui tingkat kebisingan pada angkutan umum jalur Teling-Pusat Kota Manado. Jenis penelitian ialah observasional deskrip-tif dengan desain potong lintang. Sampel berjumlah 100 kendaraan pada jalur Teling-Pusat Kota Manado. Pengukuran kebisingan dilakukan menggunakan alat Sound Level Meter. Data diolah dengan Microsoft Office Excel. Hasil penelitian mendapatkan 56 kendaraan yang menggunakan sistem audio dan 44 kendaraan tidak menggunakan sistem audio. Pada 56 kendaraan yang menggunakan sistem audio terdapat 47 kendaraan dengan tingkat kebisingan di atas nilai ambang batas kebisingan yaitu 86,05-114,15 dB dengan waktu terpapar selama 8-16 jam sedangkan pada 44 kendaraan yang tidak menggunakan sistem audio terdapat 2 kendaraan yang memiliki tingkat kebisingan di atas nilai ambang batas kebisingan yaitu 88,05-91,8 dB dengan waktu terpapar selama 10-12 jam. Simpulan penelitian ini ialah terdapat 49% kendaraan umum memiliki kebisingan di atas nilai ambang batas.Kata kunci: kebisingan, angkutan umum